Drinking Water Quality Monitoring of Sehore City (M.P) During Monsoon Season - Tejraj, Mohan; Jain, Praveen (Asian Journal of Chemistry, 2010)
The study of water quality is of enormous educational value for thequality of water and is dictated by a pattern of interaction rather than byany factors operating in isolation. The present study deals with the evaluation of drinking water quality of Sehore city (M.P.) for which 10 sampling stations of different areas were chosen. The death and decay of vegetation and animals in and around the water reservoir site contributes as a major source of pollution. Physico-chemical analysis with different parameters has been done during monsoon season 1997. The pollution of ground water in Sehore City has rached to the point of serious concern and, therefore, some preventive and curative measures must be compulsory to protect regional natural water resources and drinking water quality.